Banking on Happiness: Exploring Job Satisfaction Among Sales Employees - Yadav, Sujita Amrishbhai (Journal of Advanced Research in Entrepreneurship, Innovation and SMES Management, 2023)
Success is more likely to accrue to workers who are happy in their positions. Currently, job satisfaction is essential for employees in order to maintain the effectiveness of the company by continually motivating and engaging their workers. There are various factors for job satisfaction, such as culture, leadership communication, training and development, work-life balance, performance appraisal, rewards and benefits, compensation, working hours, work environment, career development, opportunities, etc., which can have an impact on job satisfaction adversely. Sales jobs can significantly affect mental health, according to research. Due to the high demands of their jobs and the pressure to meet their sales targets, sales professionals confront a variety of obstacles that may have an impact on their mental well-being. These challenges include stress, anxiety, and exhaustion. A person’s total well-being, particularly their mental health, has a significant impact on how they manage their work and personal lives. Reduced productivity, difficulty concentrating, and poor interpersonal interactions at work are just a few of the detrimental repercussions that poor mental health can have. Employers should therefore support staff members by offering counseling or mental health resources, encouraging work-life balance, and developing a supportive workplace culture by placing a high value on mental health, job satisfaction, and a healthy work environment.